Transcriptome Analysis Reveals Complex Defensive Mechanisms in Salt-Tolerant and Salt-Sensitive Shrub Willow Genotypes under Salinity Stress. (28th July 2020) - Sui, Dezong; Wang, Baosong
Abstract : Salinity stress is one of the most devastating abiotic stresses limiting plant growth and productivity. As a moderately salt-tolerant crop, shrub willow ( Salix spp.) is widely distributed over the world and can provide multiple bioenergy product and environmental benefits. To delve into the salt tolerance mechanism and screen out salt-tolerant genes, two shrub willow cultivars (a salt-sensitive genotype JW9-6 and a salt-tolerant genotype JW2372) at three time points (0, 2, and 12 h) after NaCl treatments were used for RNA sequencing. A comparative analysis between genotypes and time points showed 1, 706 differentially expressed genes (DEGs), of which 1, 029 and 431 DEGs were only found in the JW9-6 and JW2372, respectively. Gene Ontology (GO) and MapMan annotations suggested that many DEGs were involved in various defense-related biological pathways, including cell wall integrity, hormone signaling, antioxidant system, heat shock proteins, and transcription factors. Compared to JW9-6, JW2372 contained more DEGs involved in the maintenance of the cell wall integrity, ABA, and ethylene signal transduction pathways. In addition, more DEGs encoding heat shock proteins were found in JW2372. Instead, transcription factors including ERF, MYB, NAC, and WRKY were found to be more differentially expressed in JW9-6 under salinity stress. Furthermore, expressions of nine randomly selected DEGs were verified by qRT-PCR analysis. This study contributes in new perspicacity into underlying the salt tolerance mechanism of a shrub willow at the transcriptome level and also provides numerous salt-tolerant genes for further genetic engineering and breeding purposes in the future.